Diagnosing the Diagnostic and Statistical Manual of Mental Disorders: Fifth Edition - Cooper, Rachel (Taylor & Francis Group, 2014)
Diagnosing the Diagnostic and Statistical Manual of Mental Disorders is written for all those who wonder whether the DSM-V now classifies the right people in the right way. It is aimed at patients, mental health professionals, and academics with an interest in mental health.